Islamic Philosophy In The Contemporary Context: A Comparative Study Of The Thought Of Seyyed Hossein Nasand Syed Naquibal-attas - Tae, Soon Yim (2011)
With rapid globalization the Muslim world is facing serious challenges both from outside and inside. The challenge from outside is Western domination and secular worldview which undermines the worldview of Muslim which is the backbone of Islamic civilization. the challenge from inside is the loss of Islamic identity, especially that of Islamic intellectuality. There are two main responses to these challenge: one, the political and theological response of Islamic Fundamentalism against Western secularism, and two, the intellectual response of the movement of re-sacralization of knowledge.